Heurísticas para o problema de escalonamento de projetos com restrição de recursos - Tchao, Celso de Souza (2007)
This work considers the Resource-Constrained Project Scheduling Problem RCPSP, intending a heuristic approach about this Project Management process, the Time and Cost Management, which Project Schedule Development comprehends the timetable construction, the time and cost estimation, and the appropriate resources use over the time range considered. The problem target, in the classic version, is to minimize the project makespan, considering the precedence among activities and the limited resources availability required by each activity. This work includes two features about the traditional RCPSP: multiplicity of kind resources and multiplicity of modes for the execution of each activity, which are distinguished from each other by the duration and the resources demand. In this approach, we observed the behavior of heuristics and metaheuristics applied in the search of solutions corresponding to optimal values or close to them. Pert, CPM, SGS (Serial and Parallel) and X-Pass (Single and Multi) were chosen among the heuristics to be explained. The metaheuristics described were selected from the most known set used in recent researches. This work proposes a solution using Tabu Search and Path Relinking. The obtained results are shown and compared with other results reached by different approaches of the RCPSP.